Application of Remote Sensing Technology in Monitoring Urban Heat Island Effects - Tu, Ziyi; Wang, Zhiwen (Transactions on Environment, Energy and Earth Sciences, 2024)
As global urbanization accelerates, the Urban Heat Island (UHI) effect has become a significant problem in urban environmental studies worldwide. Traditional research methods mainly include ground-based meteorological observations and numerical simulation analyses. Ground-based meteorological observations can provide detailed local climate data but are limited in coverage, while numerical simulation can replicate urban climate features through models, although input data and modeling parameters constrain its accuracy. In contrast, remote sensing technology, with its wide coverage, high resolution, and dynamic monitoring capabilities, has emerged as a powerful tool for monitoring the UHI effect. This study explores the advantages of remote sensing technology in UHI research, emphasizing its ability to provide comprehensive spatial and temporal data, enhance the accuracy of UHI detection, and offer insights that traditional methods cannot. Key indicators of remote sensing technology, such as land surface temperature, normalized difference vegetation index (NDVI), normalized difference built-up index (NDBI), and albedo, are used to analyze the UHI effect. The primary application of remote sensing technology in UHI research includes temporal and spatial distribution changes in UHI. Technological advancements in remote sensing and data processing could further enhance the ability to monitor, analyze, and mitigate the UHI effect.